Analysis Of Community Participating Factors In Development Planning Applying The Participatory Rural Appraisal Method - Yolanda Mangunsong, Winda; Negara Lubis, Satia; Lubis, Irsyad (International Journal of Educational Research & Social Sciences, 2023)
To achieve development success in the Medan Tuntungan District, it is important to give space for community involvement. Participation of the community is the most crucial aspect in determining the success of development. The Medan Tuntungan District consists of nine villages and is one of the city's districts. In the Medan Tuntungan District of Medan City, the compilation of development planning documents is conducted utilizing a participatory method, whereby the local government prepares development program plans that the community deems essential for enhancing their well-being. Through the activities of the Development Planning Meeting, the participatory method is implemented by incorporating all parts of society and stakeholders in development planning. The purpose of this research are: (1) To assess and determine the amount of community engagement in development planning in the Medan Tuntungan District, Medan City, in terms of non-participation, tokenism, and citizen power characteristics. (2) to examine the elements that encourage and discourage community engagement in development planning in the Medan Tuntungan District of Medan City. This study employs a quantitative model using the participatory rural appraisal method and factor analysis inside the SPSS software. (1) Community participation in development planning is influenced by indicators of consultation, delegated power, and citizen control; (2) in the process of participation, the community has supporting factors such as opportunity, ability, and ability, while inhibiting factors include individual characteristics and demographic conditions.